PERANCANGAN DAN ANALISIS TEGANGAN PRESSURE VESSEL HORIZONTAL SEPARATOR DENGAN METODE ELEMEN HINGGA - Aswin Aswin; Fajar Anggara (Scientific Journal of Mechanical Engineering Kinematika, 2022)
Pressure vessel separator is a pressure vessel that functions to separate fluids in the form of water, oil, and gas which have different densities. The design of the pressure vessel in this study aims to calculate the strength and stress in the material. The design data uses secondary data in the form of datasheets and process and instrumentation diagrams that show the specifications and orientation of the pressure vessel separator. The operating pressure is 5 psi, the design pressure is 200 psi, the operating temperature is 90 F and the design temperature is 212 F. The material of the saddle, shell, and head used is SA 516 Gr.70, nozzle neck using A106 Gr. B, and nozzle flange material using SA 105. The design and analysis was carried out using manual calculations referring to the ASME section VIII standard which is the standard for pressure vessel calculations and stress analysis using Solidworks software which is software for three-dimensional image modeling and finite element analysis. The results of the design and analysis using manual calculations using the ASME section VIII standard, then the maximum allowable working pressure is 290.934 psi. Circumferential stress analysis using Solidworks software obtained 21680.2 psi and longitudinal stress obtained 25430.7 psi, so the analysis results are declared safe because they do not exceed the design pressure and allowable stress values of 38000 psi.